Strengthening Community-Based Organization to Achieve Food Security in the South Sulawesi Province - Rukmana, Novayanti Sopia; Alwi, Heriany; Halim, Didin; Pratiwi Johansyah, Oky Nur (KnE Social Sciences, 2024)
Food security is an important and urgent issue in South Sulawesi Province. To address these challenges, strengthening Community-Based Organizations (CBOs) becomes a relevant and effective strategy. This study aims to determine the strength of community-based organizations by the food security department of South Sulawesi Province. This research uses a qualitative approach. Data collection techniques are carried out by observation, interviews, and documentation. Data were analyzed using data reduction techniques, data presentation, and conclusions. The results of this study show that the empowerment of community-based organizations by the Food Safety Office of South Sulawesi Province can be seen from five indicators, namely: possibility, strengthening, protection, support, and maintenance. Based on the results of the study, four out of five empowerment indicators have been adequately met, namely: empowering, reinforcement, support, and maintenance. Protection indicators are still poorly met. The Food Safety Office of South Sulawesi Province has not fully implemented protection, especially for local food processing, so more efforts need to be made so that Women’s Group products can now be better known and can compete with other local products, especially in the South. The South Sulawesi Food Safety Office has not fully implemented protection, especially for local food processing, so more efforts need to be made so that women’s group products can now be better known and can compete with other local products. Keywords: food sustainability, empowerment, society-based organizations, women’s group now